Peranan Kelompok Tani dalam Peningkatan Pendapatan (Studi Kasus KWT Usaha Bunda Setinjau Alam Desa Simpang Talang Tembago Kecamatan Jangkat Timur Kabupaten Merangin) - Pitriani, Pitriani; Yuliardi, Fajar; Afrianto, Evo (JIA (Jurnal Ilmiah Agribisnis) : Jurnal Agribisnis dan Ilmu Sosial Ekonomi Pertanian, 2021)
This study aimed to determine the role of farmer groups in increasing coffee farmers' income and determine the level of farmers' income. This research was carried out in Simpang Talang Tembago Village, Jangkat Timur District, Merangin Regency on July 1-30, 2020. This location selection was carried out purposively considering that Simpang Talang Tembago Village is one of the significant agricultural developments in the coffee plantation sector in the District. Merangin Jambi Province is the only village with a Farmer's Group that played an important role when named the best coffee product in Indonesia at the International Coffee day 2019 event. The research method used was the Survey method which directly interviewed the management and group members. Farmer. Interviews in this study were conducted with all farmer group members, which amounted to 24 people with purposive sampling and were given questions or questionnaires. The data were analyzed using a Likert Scale. The results of the research show that the role of farmer groups in increasing the income of coffee farmers consists of 3 roles, namely social media or extension media that is lively, natural, and dynamic; tools to achieve change with the aim of agricultural extensionists; a place or container for a pure and healthy statement of aspirations following the wishes of the farmers themselves. From the research results, the role of farmer groups in influencing the income of high coffee farmers is 1035 with a score of 720-1080, and a high level of income is 505, with a category score of 384-576.